Comparison of the effectiveness of hands-on versus online education in child passenger safety. Issue 5 (28th August 2017) - Mantha, Anita; Beckworth, Kristen L; Ansiaux, John A; Chen, Carol C; Hoffman, Benjamin; Shenoi, Rohit P
Abstract : Background: Community paediatricians' knowledge of appropriate child safety seat (CSS) use in vehicles may be inadequate. We compared the effectiveness of hands-on and online education in improving and retaining child passenger safety (CPS) knowledge and skills among paediatric trainees. Methods: Paediatric trainees were randomised to receive hands-on skills training versus a 1-hour online module in CPS. CSS knowledge and installation skills were assessed using a validated 10-item/point questionnaire and an assessment tool respectively at baseline and after 6 months. Preintervention and postintervention knowledge improvement and CSS installation skills between groups were assessed using paired t-tests and effect size ( d ). Results: Forty-eight students agreed to participate and were randomised. Thirty-nine completed training (hands-on: 23 and online: 15). At entry, no significant differences in learners' demographics and prior CPS education existed. Baseline CPS knowledge scores did not differ significantly between groups (p=0.26). Postintervention, both groups demonstrated a significant increase in knowledge scores (hands-on=3.1 (95% CI 2.4 to 3.7), p<0.0001; online=2.6 (95% CI 1.9 to 3.3), p<0.0001), though the pre–post gain in knowledge scores were not significantly different between groups (p=0.35). At follow-up, both groups demonstrated a significant increase in knowledge scores (hands-on=1.8 (95% CI 1.2 to 2.4), p<0.0001; online=1.1 (95% CI 0.7 to 1.6), p<0.0001) with the hands-on group scores significantly better than the online group (p<0.02). The long-term gain in knowledge scores was not significantly different between groups (p=0.12). Baseline CSS installation skill scores did not significantly differ between groups for forward-facing seats (p=0.16) and rear-facing seats (p=0.51). At follow-up, mean CSS installation skill scores significantly increased for the hands-on group (forward-facing seat: 0.8 (95% CI 0.16 to 1.44), p<0.02; rear-facing seat: 1.2 (95% CI 0.6 to 1.7), p<0.001) but not for the online group (forward-facing seat: 0.9 (95% CI −0.08 to 1.9), p=0.07); rear-facing seat: −0.2 (95% CI −1.1 to 0.7), p=0.6). Conclusions: Among paediatric trainees, hands-on and online CPS education are both effective in improving long-term CPS knowledge. Long-term installation skills for forward-facing and rear-facing CSS persist for hands-on education but are inconclusive for online education.